2012
DOI: 10.1158/0008-5472.can-11-3831
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Autophagy Promotes Tumor Cell Survival and Adaptation to Antiangiogenic Treatment in Glioblastoma

Abstract: Anti-angiogenic therapy leads to devascularization that limits tumor growth. However, the benefits of angiogenesis inhibitors are typically transient and resistance often develops. In this study, we explored the hypothesis that hypoxia caused by anti-angiogenic therapy induces tumor cell autophagy as a cytoprotective adaptive response, thereby promoting treatment resistance. Hypoxia-induced autophagy was dependent on signaling through the HIF-1α/AMPK pathway, and treatment of hypoxic cells with autophagy inhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
342
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(362 citation statements)
references
References 44 publications
14
342
0
6
Order By: Relevance
“…Our results revealed that CoCl 2 generated a hypoxic condition and induced autophagy by increasing levels of HIF-1α, BNIP3, PI3KC3 and autophagosomal marker LC3-II in CCA cell lines. A chemical mimetic of hypoxia CoCl 2 increased autophagy has been demonstrated in several models such as in the H9c2 rat cardiomyoblast cell culture (Gallo et al, 2014) and human periodontal ligament cells (Song et al, 2012) resulting in an increasing LC3-II level that is similar to O 2 depletion induced hypoxia (Hu et al, 2012). The hypoxia induced LC3-II/LC3-I ratio has been shown that it activates autophagosome maturation (Gallo et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Our results revealed that CoCl 2 generated a hypoxic condition and induced autophagy by increasing levels of HIF-1α, BNIP3, PI3KC3 and autophagosomal marker LC3-II in CCA cell lines. A chemical mimetic of hypoxia CoCl 2 increased autophagy has been demonstrated in several models such as in the H9c2 rat cardiomyoblast cell culture (Gallo et al, 2014) and human periodontal ligament cells (Song et al, 2012) resulting in an increasing LC3-II level that is similar to O 2 depletion induced hypoxia (Hu et al, 2012). The hypoxia induced LC3-II/LC3-I ratio has been shown that it activates autophagosome maturation (Gallo et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…51,52 Previous studies have shown that HIF1A contributes to autophagy regulation in hypoxia. 20,[24][25][26][27][68][69][70] The BH3 domains of BNIP3 and BNIP3L, known HIF1A targets, disrupt the BCL2-BECN1 complex, releasing more BECN1 to be involved in the autophagic process. 24 In NP cells, although the BNIP3 level was increased under hypoxia, the absence of a concomitant increase in p-BECN1 Ser93 indicated a possible lack of correlation with autophagic induction.…”
Section: Discussionmentioning
confidence: 99%
“…Since autophagy is required for the in vivo growth of tumor cells that survive and proliferate under stress conditions such as hypoxia and nutrient deficiency, we wondered whether autophagy-blocker MIR372 can inhibit tumor growth in vivo. 28,29 The xenograft nude mice model was applied to determine the effect of stably expressed MIR372 on the in vivo tumorigenecity of breast cancer cells. Indeed, the in vivo growth of MCF7 cells with stable MIR372 expression was indeed significantly slower and the tumor mass was significantly smaller and lighter ( Fig.…”
Section: Figure 4ementioning
confidence: 99%